2018
DOI: 10.1016/j.intimp.2018.01.045
|View full text |Cite
|
Sign up to set email alerts
|

AT-RVD1 repairs mouse lung after cigarette smoke-induced emphysema via downregulation of oxidative stress by NRF2/KEAP1 pathway

Abstract: Long-term exposure to cigarette smoke (CS) results in alveolar parenchyma destruction due to chronic inflammatory response and the imbalance between oxidants and antioxidants, and proteases and antiproteases. Emphysema is the main symptom of chronic obstructive pulmonary disease. Current treatment focuses on relieving respiratory symptoms, and inflammation resolution failure is an important pathophysiological element of the disease. Specialized pro-resolving mediators (SPMs) synthesized endogenously during res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…In corneal epithelium, the role of mitogen-activated protein kinase has also been reported to mediate the epithelial repair induced SPMs. The serine/threonine kinase Akt and NrF2 signaling pathways have been described in mediating the response to SPMs in corneal and other epithelial models ( Zhang et al, 2010 ; Kenchegowda et al, 2011 ; Odusanwo et al, 2012 ; Wang L. et al, 2014 ; Posso et al, 2018 ; Zhang et al, 2018 ) ( Table 4 ).…”
Section: Impact Of Spm S Demonstrated In Cf Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In corneal epithelium, the role of mitogen-activated protein kinase has also been reported to mediate the epithelial repair induced SPMs. The serine/threonine kinase Akt and NrF2 signaling pathways have been described in mediating the response to SPMs in corneal and other epithelial models ( Zhang et al, 2010 ; Kenchegowda et al, 2011 ; Odusanwo et al, 2012 ; Wang L. et al, 2014 ; Posso et al, 2018 ; Zhang et al, 2018 ) ( Table 4 ).…”
Section: Impact Of Spm S Demonstrated In Cf Modelsmentioning
confidence: 99%
“…Antibiotics, despite their beneficial action on pulmonary function during acute infections, do not treat oxidative stress ( Wood et al, 2002 ). Although not demonstrated in CF, SPMs have been found to help reduce oxidative stress by restoring oxidant/antioxidant balance through the nuclear erythroid 2-related transcription factor 2 (Nrf2) pathway, which is defective in CF ( Posso et al, 2018 ; Zhang et al, 2018 ). In the murine model of cigarette smoke- and LPS-induced lung injury, or type 1-diabetes, RvD1 reduces ROS levels and increases antioxidant defense ( Wang L. et al, 2014 ; Posso et al, 2018 ; Zhang et al, 2018 ).…”
Section: Other Possible Impacts Of Spm S On Alterementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Posso et al demonstrated that AT-RvD1 enhanced resolution and repair in mice when given after smoking cessation. AT-RvD1 reduced oxidative stress by upregulating the Nrf2 pathway, increased IL-10 expression, and promoted restoration of lung elastin fibers (Posso, et al, 2018). In a third study, RvD1 given for 6 weeks after smoking cessation (regeneration model) had the same beneficial effect as RvD1 given during the final 6 weeks of smoke exposure (prevention model) (Kim, et al, 2016).…”
Section: Insights From Animal Models Including Therapeutic Trialsmentioning
confidence: 99%
“…Chronic cigarette smoke exposure RvD1 inhibited structural emphysema and inflammation when given concurrently with smoke exposure, and promoted lung tissue regeneration when given after smoking cessation (Kim, et al, 2016) AT-RvD1 Chronic cigarette smoke exposure AT-RvD1 promoted tissue repair by upregulating the Nrf2/Keap1 pathway (Posso, et al, 2018) LXA 4 Urban particulate matter exacerbation of allergic airway inflammation (asthma)…”
Section: Rvd1mentioning
confidence: 99%